Upaya Meningkatkan Motivasi Belajar dan Hasil Belajar Kognitif Melalui Model Problem Based Learning dan Bahan Ajar Berbasis CTL siswa kelas X SMA Negeri 8 Mandau - Maifitri Maifitri (Jurnal Bintang Pendidikan Indonesia, 2024)
The need for learning focuses on maximizing students' potential in facing today's global challenges. For this reason, a learning model that is in accordance with the demands is needed, one of which is to use the Problem Based Learning model and CTL-based teaching materials. The purpose of this study is to determine the increase in learning motivation and cognitive learning outcomes of students. This research is classroom action research. The subjects of this study were class X.1 students with a total of 36 students. While the object of this study is the motivation and cognitive learning outcomes of students after participating in learning by applying PBL learning models and CTL-based teaching materials. This type of research is Classroom Action Research (PTK) with a qualitative approach to students. The results showed that student motivation in Cycle 2 increased compared to Cycle 1, which was shown by the average value of Cycle 2 of 88.19% (very good), higher than Cycle 1 only reaching 77.07% (good). Likewise, the cognitive results of cycle 2 students also increased by 91.66% and cycle 1 by 83.33%.